Identification of cannabinoid-sensitive and -resistant oral bacteria - Scott, David A.; Lamont, Gwyneth J.; Tan, Jinlian; Patel, Arjun P.; Guffey, Jack T.; Thomas, Scott C.; Xu, Fangxi; Diamond, Gill; Saxena, Deepak (Frontiers in Microbiology, 2026)
Marijuana, an emerging risk factor for periodontitis, contains multiple potent antibacterials, particularly the phytocannabinoids. Microbial dysbiosis is a hallmark of this destructive oral disease. We examined a panel of oral bacteria for susceptibility to the major cannabinoid, cannabidiol (CBD), portended by an initial in vivo microbiome analysis of marijuana users and non-users with periodontitis. Multiple oral bacteria were found to be sensitive to physiologically relevant CBD doses–Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum, several strains of Porphyromonas gingivalis, Streptococcus mutans, Streptococcus gordonii and Tannerella forsythia. Other oral bacteria, however, were resistant to even superphysiological CBD concentrations–Campylobacter gracilis, Corynebacterium durum, Haemophilus parainfluenzae, several oral Treponema species and Veillonella parvula. Enrichment of phytocannabinoid resistant bacterial pathobionts may help explain increased periodontitis prevalence in cannabis users who, like tobacco smokers, may have distinct therapeutic and preventive needs. To this end, a library of membrane permeabilizing peptoids (N-substituted glycine oligomers), based on an endogenous mammalian antimicrobial peptide, cathelicidin, was screened for activity against Treponema denticola. This spirochete was sensitive to a sub-set of stable and inexpensive antimicrobial peptoids that, presumably due to peptoid-induced outer membrane instability, also rendered CBD toxic to normally resistant spirochetes. The tobacco-stable, cannabinoid-labile pathobiont, P. gingivalis, was also sensitive to specific antimicrobial peptoids. Electron micrographs clearly suggest altered ultrastructure in both CBD-treated P. gingivalis and peptoid-exposed T. denticola. In summary, cannabis use may promote specific oral bacteria while suppressing others. The associated dysbiosis may help explain marijuana-exacerbated periodontitis. While more comprehensive studies of cannabis-induced microbial fluxes are warranted, adjunctive antimicrobial agents, such as cathelicidin-mimicking peptoids, that target cannabis-promoted pathobionts may also be worth exploring for therapeutic potential.